الالتزام الصحي و علاقته بجودة الحياة لدى عينة من المصابين بالسكري دراسة ميدانية بالمستشفى العقيد لطفي بولاية الأغواط - سعاد بن سعد; صباح عشوري; سيرين هاجر زعابطة (My University, 2023)
h aims to know the level of health commitment and quality of life in diabetics and to reveal whether there is a correlation between health commitment and quality of life changes. The sample of the study consisted of 60 individuals with diabetes, selected in an accidental manner from within the Hospital Colonel Lutfi 240 bedsrounds, during the period from March 2023 to May 2023. The study's correlative descriptive approach was used to measure the level of variables and to determine the relationship between variables, and the data were collected by two measurements: The health commitment measure built by the students consists of 5 axes: Pharmaceutical Commitment Axis, Medical Appointments Axis, Practice Axis, Prevention Axis, Health Education Axis, World Health Organization Quality of Life Metric, Arabization (Dr. Bashura Ismail Ahmed 2008) As we have relied in our research on Spss 26 statistical data processing program, the following results have been reached: .1The level of health commitment in the sample of diabetes sufferers is high. .2The quality of life of the diabetic sample is high. .3There is no correlation between health commitment and quality of life in people with diabetes. Keywords: Commitment to Health, Quality of Life, Diabetes